Comparison of Twitch Responses During Current‐ or Voltage‐Controlled Transcutaneous Neuromuscular Electrical Stimulation. Issue 10 (October 2015) - Vargas Luna, José Luis; Krenn, Matthias; Löfler, Stefan; Kern, Helmut; Cortés R., Jorge A.; Mayr, Winfried
Abstract Neuromuscular electrical stimulation (NMES) is an established method for functional restoration of muscle function, rehabilitation, and diagnostics. In this work, NMES was applied with surface electrodes placed on the anterior thigh to identify the main differences between current‐controlled (CC) and voltage‐controlled (VC) modes. Measurements of the evoked knee extension force and the myoelectric signal of quadriceps and hamstrings were taken during stimulation with different amplitudes, pulse widths, and stimulation techniques. The stimulation pulses were rectangular and symmetric biphasic for both stimulation modes. The electrode‐tissue impedance influences the differences between CC and VC stimulation. The main difference is that for CC stimulation, variation of pulse width and amplitude influences the amount of nerve depolarization, whereas VC stimulation is only dependent on amplitude variations for pulse widths longer than 150 μs. An important remark is that these findings are strongly dependent on the characteristics of the electrode‐skin interface. In our case, we used large stimulation electrodes placed on the anterior thigh, which cause higher capacitive effects. The controllability, voltage compliance, and charge characteristics of each stimulation technique should be considered during the stimulators design. For applications that require the activation of a large amount of nerve fibers, VC is a more suitable option. In contrast, if the application requires a high controllability, then CC should be chosen prior to VC.